Vspominaia Innu Goff . Vspominaia Innu Goff . Remembering Inna Goff . Вспоминая Инну Гофф - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. A program devoted to the Soviet writer Inna Goff. Featured in the program: Okudzhava, Bulat Shalvovich (Poet); Iskander, Fazil' Abdulovich (Writer); Gamzatov, Rasul Gamzatovich (Poet); Kovalenko, Rimma (Writer); Sidorov, Evgenii (Literary Expert) Contributors: Koznova, Ol'ga (Director) Передача о советской писательнице Инне Гофф. В программе участвуют: Окуджава, Булат Шалвович (Поэт); Искандер, Фазиль Абдулович (Писатель); Гамзатов, Расул Гамзатович (Поэт); Коваленко, Римма (Писательница); Сидоров, Евгений (Литературовед) Создатели: Кознова, Ольга (Режиссер)